P-714 Visfatin and Silent Information Regulator 1 (SIRT1) in Pakistani infertile females. (30th June 2022) - Alam, F; Rehman, R
Abstract: Study question: What is the relationship of SIRT1 and oxidative stress markers with obesity among infertile Pakistani females? Summary answer: Progressive decline in antioxidants with the increase in BMI suggests that obesity causes oxidative stress that consequently leads to infertility in females. What is known already: Deficiency of Silent Information Regulator 1 (SIRT1) can trigger inflammation, mitochondrial malfunctioning and apoptosis through the hypothalamic-pituitary-ovarian axis, producing poor quality oocytes, triggering obesity and associated metabolic disorders. SIRT1 expression levels are higher in endocrine system dysfunctions. Obesity has a potential risk for subfertility, infertility, deteriorated embryo quality, decreased endometrial receptivity, implantation failure and increased miscarriage rates. Visfatin increases in response to low levels antioxidants in obese, and its expression is negatively associated with the antioxidants produced. It disturbs glucose metabolism and promotes obesity, rendering it a powerful candidate as an OS marker. Study design, size, duration: This cross-sectional study was conducted from August 2017 – July 2019, at Aga Khan Hospital in collaboration with Australian Concept Infertility Medical Centre (ACIMC) on 207 fertile and 135 infertile female subjects were recruited after ethical approval from of Aga Khan Hospital (AKU-ERC-2018-0557-601). Participants/materials, setting, methods: kg)/height in meters (m 2 ). Females were categorized by South-Asian criteria of BMI (normal-weight=18.0-22.9; overweight = 23-24.9; obese >25.0 kg/m 2 ). Commercially available ELISA kits were used for estimation of serum Manganese Superoxide Dismutase (MnSOD), Glutathione Reductase (GR), visfatin and SIRT1. Pearson Chi-Square test and ANOVA were applied to compare the means within BMI groups. Association of variables was observed by Spearman correlation with significance at p < 0.05. Main results and the role of chance: The mean BMI was 25.94 ± 5.1 kg/m 2 ; 27.5% of females were normal-weight, 22.8% overweight, while 40.9% were obese. BMI was significantly high in infertile subjects (p < 0.001). MnSOD, visfatin and GR were lower in infertile females, decreasing from normal-weight to obese (p < 0.001). Increase in BMI was associated with a decrease in SIRT1 and antioxidants levels in both fertile and infertile females. Limitations, reasons for caution: The small sample size was a limitation of the current study due to financial constraints, on the basis of which measurement of other non-enzymatic antioxidants such as malondialdehyde (MDA), glutathione, total antioxidant capacity (TAC), nitric oxide (NO) and reactive oxygen species could not be made possible. Wider implications of the findings: SIRT1 is a fascinating target in various disease situations due to the promise of pharmacological and/or natural modulators of SIRT1 activity within the framework of endocrine and immune-related disease models. Trial registration number: non applicable